“CONFLICT OF INTEREST” DALAM PENDAFTARAN MEREK DI LINGKUNGAN DJKI (STUDI KASUS ETIKA DALAM PENDAFTARAN MEREK CITAYAM FASHION WEEK) - Canggih Gumanky Farunik; Septiana Dwiputri Maharani; Annisa Daniati (Universitas Insan Budi Utomo, 2023)
Trademark registration is an effort to protect intellectual property rights (HAKI) which is regulated, approved, and managed by the Directorate General of Intellectual Property, Ministry of Law and Human Rights of the Republic of Indonesia (DJKI Kemenkumham RI). Trademark is one of intellectual property, where the problem that often occurs in trademark registration is that the trademark registrar is not the creator of the mark. This study seeks to see the Conflict of Interest behind trademark registration as an ethical issue. The urgency of this research is to determine the ethical basis to policy recommendations that can overcome conflicts of interest that occur between brand registrants and brand creation as a creative process. This research is a literature research with a case study approach of Citayam Fashion Week, to examine the Conflict of Interest between brand creators in the interest of protecting creative works and brand registrants in the interest of utilizing economic value. It is hoped that this Conflict of Interest can provide an overview of ethical issues in trademark registration, so that later it can provide policy recommendations that can help resolve disputes over intellectual property registration, especially trademarks.